The mediating role of financial well-being in the relationship between housing affordability and mental health - Veronika Jurčišinová; Catherine S. Forbes; Jason Wei Jian Ng; Tomáš Želinský (Scientific Reports)
Abstract This study examines the mediating role of financial well-being in the relationship between housing affordability and mental health across the European Union. Utilizing data from the 2018 EU Statistics on Income and Living Conditions, the analysis incorporates both objective and subjective measures of housing affordability and financial well-being. The findings reveal that financial well-being acts as a mechanism that links housing pressure to mental health, proxied by the MHI-5 Mental Health Inventory. Notably, the effect is stronger for subjective indicators, which exhibit a more pronounced mediating effect than do objective financial well-being indicators. The results underscore the importance of considering both objective and subjective dimensions in understanding the complex interplay between housing affordability, financial well-being, and mental health. The study contributes to the literature by providing insights into the underlying mechanisms through which housing affordability impacts mental health, with implications for policy interventions aimed at alleviating the negative impacts of housing affordability issues on mental health and overall well-being.